2022
DOI: 10.3389/fpubh.2022.845032
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Parents on Medication Adherence of Their Children in China: A Cross-Sectional Online Investigation Based on Health Belief Model

Abstract: ObjectiveTo explore the influence of parents on the medication adherence of their children.Study DesignA cross-sectional online investigation.MethodsA questionnaire with 41 questions was designed based on the health belief model (HBM) distributed and collected online in 28 cities around China through multi-stage stratified sampling. The reliability of the questionnaire was assessed with Cronbach's α coefficient and split-half reliability, and its validity was evaluated with exploratory factor analysis and cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Previous studies have shown that parental satisfaction with a medication is often linked to better treatment adherence. 38,39 Therefore, the data obtained from the questionnaire in this study suggests the potential for high treatment compliance, which is a crucial factor in achieving optimal outcomes in cough management. 40 The findings of this study should be considered in light of certain limitations associated with its design.…”
Section: Discussionmentioning
confidence: 86%
“…Previous studies have shown that parental satisfaction with a medication is often linked to better treatment adherence. 38,39 Therefore, the data obtained from the questionnaire in this study suggests the potential for high treatment compliance, which is a crucial factor in achieving optimal outcomes in cough management. 40 The findings of this study should be considered in light of certain limitations associated with its design.…”
Section: Discussionmentioning
confidence: 86%
“…In addition, the satisfaction questionnaire reinforces the effectiveness and safety of the tested product but also highlights the importance of patient compliance in the overall efficacy of cough treatment. 22,23 The main limitation of the study was the variance in baseline characteristics that could be attributed to the allocation method employed, which relied on the clinician's discretion. One possible explanation for this outcome is that pediatricians may have opted to administer honey-based syrup to patients with more severe or frequent cough symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…However, when we compared the mean VPA C(p) distribution across different age groups, we found significant differences, with the lowest mean C(p) in the elderly (42.4 μg/mL) and the highest in adolescents (61.4 μg/mL). This might reflect a tendency of being more careful with the dosage in older people and/or a more precise drug administration in children and adolescents involving parenting control [ 51 , 52 , 53 ].…”
Section: Discussionmentioning
confidence: 99%